(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India is an agricultural country, and animal husbandry and agriculture are inextricably linked. Agriculture provides cow fodder, while cattle excrement provides fertilizer for agriculture. Hand milking is a traditional form of milking that has been supplanted by mechanical milking equipment. The comparison analysis is conducted for three machines that perform the same job but operate in various ways: a manual press machine, only one cluster solo bucket machine, and only one bucket double clusters machine. The research also aims to better understand the operational efficiency of milking equipment for the benefit of farmers. The hand milking machine is inexpensive, but the person must perform a hand press to maintain the pressure needed for milking, while the single bucket and single cluster machines are suitable for small farmers, while the double clusters single bucket machine is more efficient than the other two because two cattle can be milked simultaneously, but the machine is more expensive. Thus, the usage of a milking machine is determined by the number of cattle on the farm, and the choice of a double clusters machine enhances milk yield while decreasing milking time.